2008
DOI: 10.1021/ja7100483
|View full text |Cite
|
Sign up to set email alerts
|

Möbius Aromaticity in N-Fused [24]Pentaphyrin upon Rh(I) Metalation

Abstract: N-fused pentaphyrins (NFP5), stable forms of meso-aryl pentaphyrins, are interesting platforms to realize Hückel aromaticity, nonaromaticity, and Möbius aromaticity depending upon the number of π-electrons, meso-substituent, and metalation. Remarkably, Rh(I) complex of pentakis(pentafluorophenyl) substituted [24]NFP5 has been characterized as a Möbius aromatic macrocycle by the crystal structure, 1H NMR spectrum, NICS calculation, and two-photon absorption (TPA) cross section. This system is, to the best of ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
91
0
7

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 140 publications
(104 citation statements)
references
References 20 publications
5
91
0
7
Order By: Relevance
“…[208,209] In contrast, attempts to prepare a fully meso-substituted pentaphyrin resulted in the isolation of N-fused systems 27def-H and 28def-H 3 . [120,162,210,211] The generality of this reaction was shown in subsequent work on Nconfused pentaphyrins, which yielded a number of singly and doubly fused macrocycles. [164,212] 27def-H and 28def-H 3 constitute two oxidation levels of N-fused pentaphyrin, corresponding to 22-and 24-electron CPs, which are interconvertible by chemical oxidation and reduction (Scheme 14).…”
Section: 1) and Their N-fusion Productsmentioning
confidence: 78%
See 1 more Smart Citation
“…[208,209] In contrast, attempts to prepare a fully meso-substituted pentaphyrin resulted in the isolation of N-fused systems 27def-H and 28def-H 3 . [120,162,210,211] The generality of this reaction was shown in subsequent work on Nconfused pentaphyrins, which yielded a number of singly and doubly fused macrocycles. [164,212] 27def-H and 28def-H 3 constitute two oxidation levels of N-fused pentaphyrin, corresponding to 22-and 24-electron CPs, which are interconvertible by chemical oxidation and reduction (Scheme 14).…”
Section: 1) and Their N-fusion Productsmentioning
confidence: 78%
“…[24] In subsequent reports it was shown that the ability to stabilize Möbius structures is a more general feature of porphyrinoids, and that the topology adopted by the macrocycle can be controlled to some extent. [25,26,103,110,[120][121][122][123][132][133][134] While the occurrences of Möbius aromaticity are still relatively rare, they are more frequent than could be expected. In fact, as we will discuss in more depth later, certain instances of Möbius topology (not always coinciding with well-defined aromatic character) were published in earlier porphyrinoid literature and remained unrecognized until recently.…”
Section: Möbius Aromaticitymentioning
confidence: 98%
“…[24] Später wurde gezeigt, dass die Fähigkeit zur Stabilisierung von Möbius-Strukturen eine allgemeine Eigenschaft der Porphyrinoide ist und die Topologie des Makrocyclus zu einem gewissen Maß kontrolliert werden kann. [25,26,103,110,[120][121][122][123][132][133][134] Möbius-Aromatizität kommt zwar relativ selten vor, aber dennoch weit häufiger, als man zunächst erwarten könnte. Weiter unten werden wir auf bestimmte Beispiele zur Möbius-Topologie, die eigentlich schon lange Bestandteil der Porphyrinoid-Literatur sind, aber bis vor kurzem nicht als solche erkannt worden waren, näher eingehen.…”
Section: Möbius-aromatizitätunclassified
“…[208,209] Beim Versuch, ein vollständig meso-substituiertes Pentaphyrin herzustellen, erhielt man lediglich die N-anellierten Systeme 27def-H und 28def-H 3 . [120,162,210,211] Diese Reaktion ließ sich verallgemeinern, denn später wurden auch N-invertierte Pentaphyrine zu einer Reihe von einfach und doppelt anellierten Makrocyclen umgesetzt. [164,212] 27def-H und 28def-H 3 sind zwei Oxidationsstufen des gleichen N-anellierten Pentaphyrins.…”
Section: ) Und Ihre N-anellierungsprodukteunclassified
See 1 more Smart Citation